The Aesthetic Features of Audience Response to Mahmoud Darwish’s Poetry - Al-Samadi, Imtenan (El Omda in Linguistics and Discourse Analysis, 2019)
This study aims at show the potentials of Rhetoric of Audience ( بلاغة الجمهور ) in approaching the responses that audiences produce to literary text in general and poetry in particular. The study tackles in particular hundreds of comments by audiences of Youtube versions of Mahmoud Darwish’s poetry. The study goal is to answer the following questions: How the structure of the poetical text with its various phonetic, syntactic lexical and semantic levels affect the responses of audiences in certain social context? What is the role of performance in forming these responses? The article answers these questions through tracing the forms of interaction between the poetical text and its receivers and analyzing their responses. Keywords: Audience responses, Rhetoric of Audience, Mahmoud Darwish, Poetry, aesthetic reception, motivating text, text producing